Development of Braille Notation Using Plasticine to Improve Musical Note Reading Competence for Blind Students - Verdian Angga Saputra (Postgraduate, University of Mataram, 2025)
This study explains the innovation of Braille music notation using plasticine learning media. The Research and Development (R&D) method was used to conduct this research through the Borg and Gall model. The population of this study involved five blind students at SMK Negeri 8 Surakarta. This study aims to develop a plasticine media product to improve the musical arts and music-reading competence of visually impaired students majoring in music at SMK Negeri 8 Surakarta. The Design and Development phase focused on creating the plasticine media, which was validated by experts in music, design, and special education, demonstrating its validity. The validation results were then processed, and the design was revised. Product testing was conducted, and the cumulative product trial results were assessed based on content quality, appearance, and technical quality, with a score of 76.38% in the feasible category. Furthermore, a feasibility test using a questionnaire administered to five students showed very positive results, with scores of 38.2 in content quality, 16.4 in appearance, and 37 in technical quality. All scores had a two-tailed significance of 0.007 and 0.013 < 0.05. These findings indicate that learning staff notation through plasticine media can improve the learning outcomes of visually impaired students.